The urgency of popular Latin American integration: the protagonism of social sciences - Costa, Everaldo Batista da (2019)
We have thought, said and written: Latin American integration can only be achieved through joint action or strategies that highlight the strength of historically oppressed social groups on the continent, that is, on the scale of the subject. Black, indigenous, mestizo, female, subalternized group resistance, etc., is what can keep the social integration utopia of Latin America standing, a region diverse from a territorial and cultural point of view. Precisely because of this paradox (integration and unity in the face of diversity and adversity) conceived at the origin, our continent is, without a doubt, the catalyst of world modernity, together with Africa and Asia, in the context of European colonization processes. Through the territory and its uses, PatryTer wishes to denounce the different forms of violence (on different scales) that our “minorized” social groups (since they are the majority of people) continue to suffer, in the face of the ideal of exclusive progress and conservative modernization, both imposed by the Western world (Europe and the United States, notably).